2017
DOI: 10.1002/ijc.30635
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps sequester circulating tumor cells via β1-integrin mediated interactions

Abstract: Despite advances in cancer treatment, metastasis remains today the main cause of cancer death. Local control through complete surgical resection of the primary tumor continues to be a key principle in cancer treatment. However, surgical interventions themselves lead to adverse oncologic outcomes and are associated with significantly increased rates of metastasis. Neutrophils through release of neutrophil extracellular traps (NETs) in response to infections were shown to be able to capture circulating cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 46 publications
4
208
0
3
Order By: Relevance
“…Our previous work has demonstrated a tumor-promoting role for NETs in preclinical models of cancer (15,32). Here, we investigate whether circulating NET levels are elevated in patients with several high-lethality malignancies, including lung, esophageal, and gastric adenocarcinoma, and we show that higher NET level is associated with disease stage.…”
Section: Introductionmentioning
confidence: 77%
“…Our previous work has demonstrated a tumor-promoting role for NETs in preclinical models of cancer (15,32). Here, we investigate whether circulating NET levels are elevated in patients with several high-lethality malignancies, including lung, esophageal, and gastric adenocarcinoma, and we show that higher NET level is associated with disease stage.…”
Section: Introductionmentioning
confidence: 77%
“…In this context, Najmeh et al have shown that β1-integrins, expressed on both tumor cells and NETs, mediate adhesion of circulating tumor cells to NETs [120]. In addition, interactions between β2-integrins on neutrophils and ICAM-1 on melanoma cells have been shown to anchor these cells to vascular endothelium, promoting extravasation [121]. Interestingly, Albrengues et al, using a murine model of experimental, tolerogenic, pulmonary tumor cell dormancy based on administration of breast cancer cell lines, observed that sustained lung inflammation caused by exposure to cigarette smoke or lipopolysaccharide triggered reactivation of dormant tumor cells [122].…”
Section: Role Of Neutrophil Extracellular Traps (Nets) In Metastasismentioning
confidence: 99%
“…α5β1 seems to play a primary role in adhesion to NETs. To this respect, a recent study reported that silencing of the β1 integrin with targeted siRNA in A549 lung cancer cells caused a decrease in cell adhesion to NETs in liver sinusoids as assessed by intravital microscopy in a mouse model of metastatic dissemination [25]. The maximal reduction of integrin-dependent adhesion to NETs was similar to that obtained after DNase 1 treatment, confirming that both DNA and fibronectin were relevant in determining cell attachment to NETs.…”
Section: Discussionmentioning
confidence: 65%